2001
DOI: 10.1039/b000754o
|View full text |Cite
|
Sign up to set email alerts
|

Saturation versus inductive effects: the electrochemistry of the C70Ph2n (n = 1–5) series

Abstract: Several arylfullerenes, C 70 Ph 2n (n = 1-5), are characterised. Their electrochemical properties, investigated by cyclic voltammetry, are the result of a competition between the electron-withdrawing effect exerted by the phenyl groups and the destabilization of redox orbitals deriving from the saturation of double bonds. C 70 Ph 2 is easier to reduce than C 70 , a feature possibly shared with C 70 Ph 4 that makes these derivatives of C 70 amongst the best electron acceptor molecules so far discovered. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…An isomer of C 70 Ph 6 was the subject of several papers in 2000 and 2001. [27,28,39] The reported NMR spectroscopic data demonstrated that the phenyl groups were arranged to give three symmetry-related pairs. For reasons that are not clear, the authors considered only the C s -p 5 -C 70 X 6 and C s -p 2 ,p 2 -C 70 X 6 addition patterns as possibilities for their compound.…”
Section: Full Papermentioning
confidence: 95%
See 2 more Smart Citations
“…An isomer of C 70 Ph 6 was the subject of several papers in 2000 and 2001. [27,28,39] The reported NMR spectroscopic data demonstrated that the phenyl groups were arranged to give three symmetry-related pairs. For reasons that are not clear, the authors considered only the C s -p 5 -C 70 X 6 and C s -p 2 ,p 2 -C 70 X 6 addition patterns as possibilities for their compound.…”
Section: Full Papermentioning
confidence: 95%
“…For example, in one paper the mismatch between the number of sp 2 13 C resonances for C 70 Ph 6 and the number expected for the "most likely" C s -p 5 structure was explained away as "probably due to signal coincidence" despite the fact that the C 2 -p 5 structure would naturally give rise to fewer signals. [28] Furthermore, in another paper the small S 0 -S 1 energy gap predicted [27] for C s -p 5 -C 70 Ph 6 required that its fluorescence at 728 nm was due to a highly unusual radiative relaxation from an S 2 state instead of from the S 1 state. [27] Our DFT HOMO-LUMO gaps for C s -p 5 -and C 2 -p 5 -C 70 Ph 6 are 0.49 and 1.41 eV, respectively, so once again the reported data are better explained by assuming that the isomer of C 70 Ph 6 that has been isolated and studied in the past [27,28,39] is in fact the C 2 -p 5 isomer.…”
Section: Full Papermentioning
confidence: 98%
See 1 more Smart Citation
“…We note that isomer 2 is the thermodynamically more stable compound but, from kinetic considerations, formation of isomer 1, characterised by successive 1,4 additions, may be favoured. [19] Both this study and that of Coheur et al [19] support regioisomer 2 rather than isomer 1, which was predicted from NMR data [17] as being the most probable structure of C 70 Ph 6 . Figure 3 g shows large phenyl contributions of about 30 % in the EDV spectrum at E 1.57 and 2.35 eV (790 and 528 nm).…”
Section: Triplet-state Absorption Spectramentioning
confidence: 58%
“…[17] The predicted regioisomer of C 70 Ph 4 has a fullerene cage-centred chromophore consisting of 20 six-membered and 8 five-membered carbon rings. The C 70 molecule itself contains 25 hexagons and 12 pentagons.…”
mentioning
confidence: 99%